دور منصة ووردوال في تعليم المفردات العربية لغير الناطقين بها: دراسة مكتبية تحليلية - Hadi, Syamsul; Agny Anggara, Syamfa (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2026)
Over the past twenty years, advancements in digital technology have significantly transformed language learning, including Arabic instruction for non-native speakers. While previous research has shown that Wordwall can enhance learning outcomes and boost student motivation, these studies mainly focus on practical aspects and do not thoroughly explore its connection with Second Language Acquisition theory. This creates a need for a more comprehensive conceptual analysis. This article examines how Wordwall supports Arabic vocabulary learning among non-native learners through a literature review. It investigates its features, teaching principles, and alignment with Second Language Acquisition theories. The study uses a library research approach with critical analysis, involving stages like identifying the problem, selecting academic sources, evaluating literature, organizing findings, and synthesizing insights. Findings suggest that Wordwall serves both as a gamified platform for vocabulary practice and assessment. It offers meaningful input, instant feedback, repetitive practice, and interactivity, all of which aid in vocabulary understanding and retention. Additionally, Wordwall aligns with key Second Language Acquisition principles, including input, output, and memory reinforcement. Theoretically this study contributes by explaining the relationship between gamified digital media and the principle of second language acquisition in the Arabic vocabulary learning. Practically, it provides pedagogical insights for Arabic teachers and curriculum designers on how to integrate interactive digital platforms into the modern Arabic learning.